GP83 Foetal valproate syndrome, developing a new service. (June 2019) - Geraghty, Jennifer; Sokay, Anitha; Kalim, Attia
Abstract : Introduction: A Paediatric valproate clinic at Our Lady's Children's Hospital Crumlin was established to assess those children who were exposed to sodium valproate antenatally in Ireland and to determine if this exposure is the contributing factor to their developmental delay, autism or skeletal malformations. Antiepileptic drugs (AEDs) have been associated with a two to three fold increase in major malformations in children exposed to AEDs in-utero, compared to the general population. 1–2 Children exposed to sodium valproate compared to other AEDs had the highest level of risk of a malformation at 10.93%. 3 Methods: A national referral service was established via the HSE Valproate Support Team. GP were advised to refer all children less than sixteen years of age exposed to valproate antenatally. Thirteen children from six families were reviewed in the first six weeks. Background diagnosis, developmental history, maternal valproate history and full clinical examination findings were noted. Data was collected and recorded via a proforma. Results: Ages ranged from two to fifteen years, mean age of nine years. Two were exposed to lamotrigine along with valproate. Valproate dosages ranged from 500 mg to 1 gram twice a day. Only three mothers were counselled regarding potential side effects of valproate exposure antenatally. Dose was adjusted in four cases, increased on two occasions and decreased on two. Two children have been diagnosed with dyspraxia and dyslexia, one has ADHD and eight have autism. All have some form of developmental delay. Slight facial dysmorphism was noted in sixty percent of these children. Thirty percent children were breast fed for different duration, while mums remained on valproate. All were referred to Geneticist after taking their blood samples for microarray and fragile X, for the final diagnosis of foetal valproate syndrome. Conclusion: Valproate has a significant role in causing global developmental delay, autism and congenital malformation. There is an urgent need to take necessary actions in order to stop its use in women of childbearing age and especially in pregnancy. References: Peacrce JMS. Acromegaly. In: Fragments of neurological history. London: Imperial College Press, 2003:501–9. Pearce JMS. Howard Henry Tooth ( 1856–1925). J Neurol 2000; 247:3–4. Weston J, Bromley R, Jackson CF, Adab N, Clayton-Smith J, Greenhalgh J, Hounsome J, McKay AJ, Tudur Smith C, Marson AG ( 2016) Monotherapy treatment of epilepsy in pregnancy: congenital malformation outcomes in the child. Cochrane Database Syst Rev . https://doi.org/10.1002/14651858.CD010224.pub2